PENGARUH E-WOM DAN CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION MELALUI KEPUASAN PELANGGAN TOKOPEDIA - Nurcahyo Ramadhan (2022)
This research is a type of quantitative research that aims to determine the effect of e-WOM and customer experience on repurchase intention through customer satisfaction. This study uses primary data sources. The sample used in this study was 100 respondents with a population of Tokopedia users who live in the South No. area. Sampling in this study using non-probability sampling with purposive sampling technique. Data collection in this study was carried out by distributing questionnaires online using Google Forms via social media. The hypothesis test in this study uses the partial least squares method. The results of this study were (1)e-wom variable had No. effect on repurchase intention with a sample origin value of 0.204, (2)customer experience variable had an effect on repurchase intention with a sample origin value of 0.307, (3)customer satisfaction variable had an effect on repurchase intention with a sample origin value of 0.359, (4)e-wom variable does not affect repurchase intention through customer satisfaction with a sample origin value of 0.070, (5)customer experience variable influences repurchase intention through customer satisfaction with a sample origin value of 0.238.